A new species of Poecilanthe (Leguminosae, Papilionoideae, Brongniartieae) from Southeastern Brazil - Meireles, Jose Eduardo; de Lima, Haroldo Cavalcante (Phytotaxa, 2013)
A new legume species from Southeastern Brazil, Poecilanthe fluminensis, is described and illustrated. It is readily distinguished from the remaining species of the genus by a combination of exclusively unifoliolate leaves with very short petioles (5–9 mm long), red calyx, and strongly dimorphic anthers (short anthers less than ¾ of the length of the longer ones). The new species, P. fluminensis, appears to be endemic to Rio de Janeiro State, Southeastern Brazil.